(untitled) (International Journal of Environmental Sciences, 2025)
The aim of this research is to investigate the act of auditor switching at the eastern Indonesian Regional Development Bank (BPD). There are several factors that influence auditor switching, including the issuance of a going concern opinion, financial distress, audit tenure, and changes in company management. The data was obtained from the published financial statements of the Regional Development Bank (BPD) and the results of the Focus Group Discussion (FGD). This research uses a quantitative approach by analyzing secondary data in the form of the financial statements of Regional Development Banks (BPD) from 2017 to 2022, using logistic regression techniques. The findings showed that, in contrast to financial hardship and audit tenure, going concern opinions and changes in management have an impact on auditor switching. This provides an explanation of how changes in banking management (BTN) and the going concern opinion that was given to an auditor can affect auditor switching. Conversely, financial distress and audit tenure experienced by the company have no impact on auditor switching. This research can provide recommendations on business management and improving the quality of financial statements in BPD. Additionally, it can also provide references for regulators regarding auditor switching practices carried outby banks in Indonesia.